Recent Development in Ammonia Stripping Process for Industrial Wastewater Treatment - Lennevey, Kinidi; Ivy Tan, Ai Wei; Noraziah, Abdul Wahab; Khairul Fikri, Tamrin; Cirilo, Nolasco-Hipólito; Shanti Faridah, Salleh (Hindawi Publishing, 2018)
t is noteworthy to highlight that ammonia nitrogen contamination in wastewater has been reported to pose a great threat to theenvironment. -is conventional method of remediating ammonia nitrogen contamination in wastewater applies the packed bedtower technology. Nevertheless, this technology appears to pose several application issues. Over the years, researchers have testedvarious types of ammonia stripping process to overcome the shortcomings of the conventional ammonia stripping technology. Alongthis line, the present study highlights the recent development of ammonia stripping process for industrial wastewater treatment. Inaddition, this study reviews ammonia stripping application for varied types of industrial wastewater and several signiﬁcant operatingparameters. Furthermore, this paper discusses some issues related to the conventional ammonia stripper for industrial treatmentapplication. Finally, this study explicates the future prospects of the ammonia stripping method. -is review, hence, contributes byenhancing the ammonia stripping treatment eﬃciency and its application for industrial wastewater treatment.